Toxicities and outcome after CD19-directed chimeric antigen receptor T-cell therapy for secondary neurolymphomatosis - Kaulen, Leon D.; Karschnia, Philipp; Doubrovinskaia, Sofia; Abramson, Jeremy S.; Martinez-Lage, Maria; Shankar, Ganesh; Choi, Bryan D.; Barnes, Jeffrey A.; El-Jawahri, Areej; Hochberg, Ephraim P.; Johnson, P. Connor; Soumerai, Jacob D.; et al. (American journal of hematology, 2024)
Lymphomatous infiltration of the peripheral nervous system (PNS), termed neurolymphomatosis, represents a distinct extranodal non-Hodgkin lymphoma variant with dismal outcome. CD19-directed chimeric antigen receptor (CD19-CAR) T-cell therapy has emerged as a safe and effective treatment for B-cell lymphomas. We aimed to assess toxicity and efficacy of CD19-CAR T-cells in neurolymphomatosis. Neurolymphomatosis patients treated with CD19 CAR T-cells were retrospectively identified at Massachusetts General Hospital over a six-year period. Toxicities were graded according to the ASTCT classification, management, and response rates were recorded. Eleven neurolymphomatosis patients were identified with a median of 2 lines of PNS-directed treatments (range: 1-3) prior to receiving CD19-CAR T-cells. Neurolymphomatosis localized to the nerve roots (8/11, 73%), plexus (5/11, 45%), peripheral (4/11, 36%) and cranial nerves (5/11, 45%). Low grade cytokine release syndrome (CRS) was detected in 8/11 (73%; grade 1: N = 7; grade 2: N = 1) cases. Low- and high-grade immune cell-associated neurotoxicity syndrome (ICANS) were recorded in 5/11 (45%; grade 1: N = 4; grade 2: N = 1) and 1/11 (9%; grade 4) patients, respectively. CRP levels at infusion were predictive of ICANS (area under the curve: 0.96, p = 0.01). Seven of eleven neurolymphomatosis patients (64%) responded to CD19-CAR T-cells. Complete remissions (CR) were achieved in three cases (27%), with 2 patients in sustained CR nine and 46 months after CD19-CAR infusion. Median progression-free survival (PFS) was 4 months. Collectively, CD19-CAR T-cell treatment was well tolerated and showed promising efficacy in recurrent neurolymphomatosis, a difficult to treat condition with unmet medical need. Findings suggest that CD19-CAR may sufficiently penetrate the blood-nerve barrier. Toxicity and outcomes were overall similar to CAR-T cell therapy in CNS lymphoma.
Gesehen am 12.05.2025